Wear and corrosion behavior of multi-walled carbon nanotubes (MWCNTs) reinforced Al-15Mg2Si in-situ composites. (6th September 2019) - Zengin, Huseyin
Abstract: In this study, Al-15Mg2 Si and Al-15Mg2 Si-MWCNT composites were produced by a combination of semi powder metallurgy and stir casting processes and microstructure, wear and corrosion properties were investigated. MWCNTs were selected as the ideal reinforcement in this study since they possess high specific modulus and high specific strength. The first step of the production of MWCNT-containing composites was to prepare Al-MWCNT samples by a vacuum distillation setup, followed by sintering under argon gas atmosphere. Then, the prepared Al-MWCNT ingots were added to Al-15Mg2 Si melt and mixed by mechanical stirring. Microstructural characterizations were carried out by x-ray diffraction (XRD), optical and scanning electron microscopies (SEM). Wear tests were conducted by reciprocating apparatus under different applied loads. Corrosion behaviors were characterized by immersion and potentiodynamic polarization tests. The results showed that large and irregular primary Mg2 Si phases were formed in both composites with surrounding Chinese-script like eutectic Mg2 Si phases. The volume fraction of primary Mg2 Si phase in the Al-15Mg2 Si composite increased after MWCNT addition. The Al-15Mg2 Si-MWCNT composite exhibited significantly higher wear resistance than the Al-15Mg2 Si composite. Both immersion and potentiodynamic polarization tests revealed that the corrosion resistance of Al-15Mg2Si composite deteriorated by MWCNT addition.